2011
DOI: 10.1038/nrrheum.2010.225
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing programmed cell death as a therapeutic strategy in rheumatic diseases

Abstract: Programmed Cell Death (PCD) is a key process regulating immune cell development and peripheral immune homeostasis. Caspase-dependent apoptosis as well as a number of alternative cell death mechanisms account for immune cell PCD induced by cell-intrinsic as well as extrinsic pathways. In animal models, compelling evidence has emerged that genetic defects in programmed cell death can result in autoimmune disease. Autoimmune disease can arise from single-gene mutations affecting PCD, and defective PCD has been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…Furthermore, knowledge of the pathogenic pathways of CD4 T‐cell destruction is a prerequisite for designing novel treatment strategies in order to improve immune recovery. The therapeutic implications of modulating programmed cell death by specific inhibitors are already under active investigation in preclinical and clinical trials for other entities, such as pancreatic cancer and rheumatic diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knowledge of the pathogenic pathways of CD4 T‐cell destruction is a prerequisite for designing novel treatment strategies in order to improve immune recovery. The therapeutic implications of modulating programmed cell death by specific inhibitors are already under active investigation in preclinical and clinical trials for other entities, such as pancreatic cancer and rheumatic diseases .…”
Section: Discussionmentioning
confidence: 99%
“…60,61 essential to avoid the outflow of intracellular content and limit the immunological response against generated antigens. 62,63 However, under some circumstances, apoptotic bodies and fragments can constitute a major source of immunogens in autoimmune diseases that involve the targeting of ubiquitous autoantigens. [64][65][66] Apoptosis of BECs in PBC has been investigated in several studies; it has been demonstrated that cholangiocytes from PBC patients show increased deoxyribonucleic acid (DNA) fragmentation and significantly greater levels of Fas, FasL, perforin, granzyme B, and TNF-related apoptosis-inducing ligand.…”
Section: The Immunobiology Of Cholangiocytesmentioning
confidence: 99%
“…Apoptosis is a representative type of programmed cell death, which is different from necrosis or autophagy . Apoptosis is triggered by extrinsic signals mediated by cell‐surface receptors such as tumor necrosis factor receptor (TNF), Fas, and the receptor for TNF‐related apoptosis‐inducing ligand (TRAIL) and by intrinsic pathways induced by DNA damage, cellular stresses or withdrawal of cytokines . Induction of extrinsic pathway by death receptors (TNF receptor, Fas, or TRAIL receptor) activate procaspase 8, which induces apoptosis via caspase activation (Fig.…”
Section: Apoptosismentioning
confidence: 99%